Reduction of threading dislocation by recoating GaN island surface with SiN for high‐efficiency GaN‐on‐Si‐based LED. Issue 3 (28th January 2014) - Hikosaka, Toshiki; Yoshida, Hisashi; Sugiyama, Naoharu; Nunoue, Shinya
Abstract: We have demonstrated low‐threading‐dislocation‐density (low‐TDD) GaN grown on Si substrate using the technique of multiple modulation of dislocation behavior that combines GaN island formation on SiN interlayer with recoating GaN island surface with SiN cap layer. TEM analysis showed the dislocation bending and/or blocking is brought about at the surface of GaN islands by recoating GaN island surface with SiN cap layer. TDD was found to be as low as 2.6×10 8 /cm 2 with FWHMs of 289 and 256 arcsec for (0002) and (10–12) X‐ray rocking curves (XRCs), respectively, which is a value comparable to that for GaN grown on a sapphire substrate. By reducing TDD, the light output power at 20 mA (12.5 A/cm 2 ) was enhanced by a factor of 1.5 and the maximum EQE increased up to 59% for the blue LED. This result indicates that the reduction of TDD is an effective approach for obtaining the high‐efficiency GaN‐on‐Si‐based LED. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)